PERMINTAAN GULA DI INDONESIA* - Sugiyanto, Catur (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2007)
This paper examines the Indonesian demand for sugar. The issue revive because of the high price of domestic sugar and the anomaly due to the domestic respon of the producer. Sugar is consumed directly by the household and indirectly through the processed food which use sugar as an ingredient. We use annual data from 1973 to 2002 and cross sectional data from SUSENAS 2003. The (short-run) estimate elasticity of demand for Sugar deacreasees and approaches to 0.46 while the long-run is small (0,02). Overall, the total demand for sugar increase due to the increasing number of population.